Mercury wet deposition in the urban and industrialised region of Campinas, south-east Brazil - Hechavarria-Hernandez, Amauris; Viana, José Lucas Martins [UNESP]; Fostier, Anne Hélène (CSIRO Publishing, 2025)
Environmental context Wet deposition is a primary mechanism for transferring atmospheric mercury (Hg) to Earth’s surface. In Brazil, as well as in the rest of the Southern Hemisphere, only limited data on wet Hg deposition are available. This article addresses this gap by providing a comprehensive dataset from nearly 2 years of monitoring, focusing on mercury concentrations in rainwater and wet Hg deposition in Campinas, one of the largest industrial and populated regions in São Paulo state (south-east Brazil). Rationale Data on mercury (Hg) wet deposition in Brazil, as well as in the rest of the Southern Hemisphere, are sparse. To fill this gap, this study presents a comprehensive dataset from a long-term monitoring effort (nearly 2 years) that focuses on Hg concentrations in rainwater and wet Hg deposition in Campinas, one of Brazil’s largest industrial and populated regions located in São Paulo state (south-east Brazil). Methodology A total of 66 rain events were captured from April 2019 to December 2020 using a manually operated rain collector. The total Hg concentration was determined using Cold Vapour Atomic Fluorescence Spectrometry (CVAFS), and wet Hg deposition was calculated. Results The volume-weighted mean (VWM) Hg concentration ranged from 5.59 to 15.3 ng L−1, with the highest value recorded during the driest season; the overall average for the sampling period was 6.42 ng L−1. Annual Hg wet deposition varied from 6.5 to 7.1 µg m−2 year−1. Discussion These results indicate a clear seasonal variation in Hg deposition and suggest that precipitation depth is the primary influencing factor at our study site. Both the VWM and Hg deposition levels were comparable to those observed in many urban and industrial sites in the Northern Hemisphere. More long-term wet deposition monitoring is needed in urban and industrialised areas of the Southern Hemisphere to improve our understanding of the impacts of human activities on the Hg cycle.